Clinical immunotherapy in glioma: current concepts, challenges, and future perspectives - Liu, Jun; Peng, Jingjian; Jiang, Jian; Liu, Yanhui (Frontiers in Immunology, 2024)
Glioma is one of the common tumors in the central nervous system, and its treatment methods (surgery, radiotherapy, and chemotherapy) lack specificity and have a poor prognosis. With the development of immunology, cell biology, and genomics, tumor immunotherapy has ushered in a new era of tumor therapy, achieving significant results in other invasive cancers such as advanced melanoma and advanced non-small cell lung cancer. Currently, the clinical trials of immunotherapy in glioma are also progressing rapidly. Here, this review summarizes promising immunotherapy methods in recent years, reviews the current status of clinical trials, and discusses the challenges and prospects of glioma immunotherapy.